Covert dissemination of pLVPK-like virulence plasmid in ST29-K54 Klebsiella pneumoniae: emergence of low virulence phenotype strains - Qiu, Jiehui; Wei, Dandan; Ma, Jiaxin; Liu, Ren; Shi, Jianglong; Ren, Qun; Wei, Chunping; Huo, Binghui; Zhu, Lanlan; Xiang, Tianxin; Liu, Yang; Cheng, Na (Frontiers in Cellular and Infection Microbiology, 2023)
This study aimed to explore the epidemic, clinical characteristics, and molecular and virulence attributes of Klebsiella pneumoniae serotype K54 (K54-Kp). A retrospective study was conducted on 328 strains of Klebsiella pneumoniae screened in a Chinese hospital from January 2016 to December 2019. The virulence genes and antibiotic resistance genes (ARGs) were detected by PCR, and a drug sensitivity test was adopted to detect drug resistance. Multilocus sequence typing (MLST) and PFGE were performed to determine the clonal correlation between isolates. Biofilm formation assay, serum complement-mediated killing, and Galleria mellonella infection were used to characterize the virulence potential. Our results showed that thirty strains of K54-Kp were screened from 328 strains of bacteria, with an annual detection rate of 2.29%. K54-Kp had a high resistance rate to antibiotics commonly used in the clinic, and patients with hepatobiliary diseases were prone to K54-Kp infection. MLST typing showed 10 sequence typing, mainly ST29 (11/30), which concentrated in the B2 cluster. K54-Kp primarily carried virulence genes of aerobactin, silS, allS, wcaG, wabG, and mrkD, among which the terW gene was closely related to ST29 (p<0.05). The strains infected by the bloodstream had strong biofilm formation ability (p<0.05). Most strains were sensitive to serum. Still, the virulence of pLVPK-like virulence plasmid in ST29-K54 Klebsiella pneumoniae was lower than that of ST11 type and NTUH-K2044 in the Galleria mellonella model. Therefore, these findings supply a foundation to roundly comprehend K54-Kp, and clinicians should strengthen supervision and attention.